Analysis of the impact of digital and financial development of the country on its economic growth on the example of Belarus - Gospodarik, Catherine G.; Losyakina, Polina V. (Journal of the Belarusian State University. Economics, 2022)
The article is a continuation of the author’s research on the impact of financial development and the spread of digital technologies on economic growth. An econometric model of economic growth, taking into account digital and financial development, is built on the example of the Belarus.